If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -10 = -3p + 3 + 4p Reorder the terms: -10 = 3 + -3p + 4p Combine like terms: -3p + 4p = 1p -10 = 3 + 1p Solving -10 = 3 + 1p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -10 + -1p = 3 + 1p + -1p Combine like terms: 1p + -1p = 0 -10 + -1p = 3 + 0 -10 + -1p = 3 Add '10' to each side of the equation. -10 + 10 + -1p = 3 + 10 Combine like terms: -10 + 10 = 0 0 + -1p = 3 + 10 -1p = 3 + 10 Combine like terms: 3 + 10 = 13 -1p = 13 Divide each side by '-1'. p = -13 Simplifying p = -13
| 2cos(x)=-2cos(2x) | | 4x-10+3x+10=180 | | 8(2x-3)=3x-12 | | 2cos(x)=-2cost(2x) | | ln(7x-4)=8 | | 2+87=7-8 | | 3x-12x+12=60 | | 0.499x-974.6= | | 7-8x=-7-5 | | 784-25x=817-36x | | 4-(3x-4)-3=5x-2(x-5)-4 | | 3g+3[-6+2g]=1-g | | 4x-3x-15=7 | | .6x+3.5=.67x+.33 | | 11x+16y+10=0 | | 114=3x+4(x+11) | | -2v+-7=7 | | -x-(-2)=1 | | 6x+11=-31-8 | | 4n^2+4n+1=20 | | 3x+(-x+1)-x-5=8-(2x-6+x) | | Qx^2+qx+5-q=0 | | -6=2g+8 | | 36-x=-6 | | 6t-72=7t-84 | | 60-5x=80-13x | | 8n-[4n+5]=3 | | 10b-2(b+3)=56 | | (x+1)(x-2)+2x=(x-3)(x+2) | | -22=7x+22 | | 6x+8+6x=140 | | x^2+0.06x=0.028 |